LANGUAGE EDUCATION TRENDS IN UKRAINE (LATE ΧΧ – EARLY ΧΧΙ) - Korotkova, Yuliia (The Modern Higher Education Review, 2019)
The article is devoted to the distinction and characterization of the leading trends in the development of language education in Ukraine in the late XX – early XXI centuries, which include: strengthening the authority of the Ukrainian language, its dissemination in all spheres of public life; increasing attention to foreign languages; a gradual transition to linguistic diversity and multilingualism; paying special attention to the study of the Ukrainian language as a foreign language; launching a certification process for the level of knowledge in Ukrainian and foreign languages; constant updating of the purpose, tasks, content, forms, methods and means of language education.